Intertwining organisational learning and institutional settings: Evidence from organisational case studies in East German context - Mike Geppert (Journal for East European Management Studies, 2002)
This paper is an attempt to develop a less normative conception of organisational learning which allows for more practice-oriented research on the topic. Our research, conducted in East-German companies in the context of societal transformation, can be understood as a process of building a particular understanding of organisational learning through the use of multiple case studies. With our comparative research framework we will show how key actors and strategically dominant groups of actors socially construct the opportunities and constraints that they experience in the process of organisational learning within a context of macro-level structures previously enacted. In conclusion, we underline the benefits of the enactment perspective developed here and its use in analysing paths of organisational learning. – – In diesem Artikel wird der Versuch unternommen, ein weniger normatives Verständnis von Organisationslernen, als das in vielen Publikationen zu dieser Thematik der Fall ist, zu entwickeln. Dabei wird insbesondere die Fragestellung untersucht, inwieweit die institutionelle Einbettung von ostdeutschen Unternehmen die Ausrichtung und den Verlauf organisationalen Lernens beeinflusst. Die vergleichende Fallstudiennalyse hat gezeigt, daß die Akteure und Akteursgruppen ihre Lernmöglichkeiten und auch -barrieren im Prozeß interaktiven Lernens selbst sozial konstruieren. In diesem Sinne wird abschließend vorgeschlagen, daß künftige Untersuchungen zu diesem Thema auf institutionell vermittelte und damit eher verschiedenartige Pfade organisatorischen Lernens fokussieren sollten.
Keywords: 650